Becoming‐urban, becoming‐forest: a historical geography of urban forest projects in Australia. (16th January 2016) - Jones, Ryan; Instone, Lesley
Abstract: In recent times, local governments in Australia's major cities have embraced the idea that the trees in their streets, parks, and private gardens are parts of a collective urban forest that can be managed to address complex policy problems and create more liveable and sustainable cities. In light of this proposition, applied and critical urban forest researchers have typically focused on questions of quantity with regard to some of the factors that influence the density and distribution of urban tree cover. In a few cases, however, researchers have documented qualitative changes to the urban trees and woodlands that ostensibly constitute the urban forest, suggesting that it might be apprehended in a more mutable and dynamic way. Building on these accounts, we turn to Deleuze and Guattari's theory of becoming to read the urban forest in an active and malleable light, developing a historical geography of urban forestry in Australia that discerns three urban forest projects we call the 'forest in a city', the 'city forest', and a new but not yet realised, 'city in a forest'. This finding renders the urban forest in more contingent, multiple, and mutable terms, leading us to finish the paper with a consideration of what seeing the urban forest as becoming means for future research. There, we suggest that Deleuze and Guattari's becoming directs us to different kinds of empirical, political, and ethical concerns that haven't received significant interest in the current literature. These include asking how, why, and with what consequences do particular styles of urban forestry emerge at particular space‐times. How is qualitative difference and urban forest multiplicity dealt with in practice, as well as focusing on affect and everyday embodied encounters between people and trees in different urban places.